Curriculum Policy of Islamic Studies Based on Arabic Language at Ora Aji Islamic Boarding School Yogyakarta - Maulida, Ghina Rahmah; Maarif, Arsyad Khoirul; Sabarudin, Sabarudin (Tadarus Tarbawy : Jurnal Kajian Islam dan Pendidikan, 2025)
This research aims to investigate the curriculum and evaluate the implementation of Arabic language learning and understand the various challenges at the Ora Aji Islamic Boarding School, Yogyakarta. The research method used is qualitative with a case study approach. The selection of informants was carried out using purposive sampling, a data sampling technique that considers certain factors. The research instrument consists of in-depth interviews, document analysis, and observation. Data analysis uses the Miles and Huberman interactive model. The findings involve several aspects, including a lack of innovation and motivation in teaching Arabic, low effectiveness of Arabic language application, and a shortage of Human Resources (HR). Learning Arabic at Madrasah Aliyah (MA) has proven to be effective inside and outside the classroom (dormitory). It is recommended that Arabic language teaching not only be limited to the classroom, but also implemented in dormitories using the muhadasah method and delivering vocabulary for at least 1 day and 3 vocabularies (mufrodat). Even though the Ora Aji Islamic Boarding School tries to combine Salafi and modern teaching methods, the implementation of Arabic in classes and dormitories is still hampered. The importance of consistency and consequences for students who violate Arabic language rules shows that the Ora Aji Islamic Boarding School is still in the stage of development and adjustment to the characteristics of each student.